ANALISIS KESELAMATAN DAN KESEHATAN KERJA PADA BAGIAN PRODUKSI MENGGUNAKAN METODE 5S DALAM KONSEP KAIZEN DI PT. SWABINA GATRA - Ikhwatun Khasanah; Akhmad Wasiur Rizqi; Hidayat (Jurusan Teknik Industri, Institut Sains & Teknologi AKPRIND Yogyakarta, 2022)
Occupational Health and Safety (K3) is a branch of science and application that studies how to prevent accidents in the workplace. One of the companies closely related to this program is PT. Swabina Gatra. Where this company is engaged in the manufacturing business in the form of